Identifying electronic-sport athletes` sleep-wake cycle characteristics - Gomes, M. A.; Veruska Narciso, F.; de Mello, M. T.; Maculano Esteves, A. (Chronobiology International, 2021)
Organized electronic-sport competitions (e-Sport) is related to several health problems, including sleep disorders. The objective of this study was to evaluate the characteristics of the sleep-wake cycle of League of Legends (LoL) athletes during their pre-training, training, pre-competition, and competition routines. Twenty male elite LoL players completed the questionnaires related to sleep pattern (Pittsburgh Sleep Quality Index), sleepiness (Epworth Sleepiness Scale), and chronotype (Morningness-Eveningness Questionnaire), and they wore an actigraph for 7 days. Pre-training and pre-competition assessments were carried out by questionnaires (n = 20) and training and competition assessments by actigraph (n = 16). The chronotype that most Eathletes presented was a moderately evening type. They presented a poor sleep quality and were borderline for excessive daytime sleepiness. Sleep onset and offset times were significantly prolonged during the competition condition (t = 2.11, p < .05; t = 2.51, p < .05). Correlations showed a relationship between PSQI and Sleepiness in the pre-training and pre-competition conditions (r = 0.50, p = .02) and chronotype with sleep onset (r = 0.61, p = .01), total sleep time (r = 0.55, p = .02), and time awake (r = 0.49, p = .04) in the competition condition. Linear regression analysis indicated associations between the PSQI and sleepiness (25%; p = .02) during pre-training and pre-competition. During the competition there were associations between chronotype and sleep onset (37%; p = .01), chronotype and time awake (24%; p = .04), and chronotype and TST (30%; p = .02). In general, the findings support the conclusion that LoL athletes presented an altered sleep pattern during their training routines.